The role of BRAF mutations in primary melanoma growth rate and survival. (1st July 2015) - Mar, V.J.; Liu, W.; Devitt, B.; Wong, S.Q.; Dobrovic, A.; McArthur, G.A.; Wolfe, R.; Kelly, J.W.
Summary: Background: The clinical behaviour and prognosis of primary melanomas harbouring BRAF mutations is not fully understood. Objectives: To investigate the effect of mutation status on primary melanoma growth rate and melanoma‐specific survival (MSS). Methods: A prospective cohort of 196 patients with stage I–III primary cutaneous melanoma were followed for a median of 92 months, pre‐dating the institution of BRAF inhibitor therapy. Clinicopathological variables were correlated with mutation status and hazard ratios (HRs) estimated for MSS. Results: Of 196 tumours, 77 (39·2%) were BRAF V600E, 10 (5·1%) BRAF V600K and 33 (16·8%) were NRAS mutant. BRAF V600E mutant melanomas were associated with favourable clinical characteristics and tended to be slower growing compared with BRAF V600K, NRAS mutant or BRAF/NRAS wild‐type tumours (0·12 mm per month, 0·61 mm per month, 0·36 mm per month and 0·23 mm per month, respectively; P = 0·05). There were 39 melanoma deaths, and BRAF mutant melanomas were associated with poorer MSS in stage I–III disease [HR 2·60, 95% confidence interval (CI) 1·20–5·63; P = 0·02] and stage I–II disease (HR 3·39, 95% CI 1·12–10·22; P = 0·03) after adjusting for other prognostic variables. Considered separately, BRAF V600E mutant melanomas were strongly associated with MSS independently of thickness and nodal status (HR 3·89, 95% CI 1·67–9·09; P < 0·01) but BRAF V600K mutant tumours were not (HR 1·19, 95% CI 0·36–3·92; P = 0·77). Conclusions: The presence of a BRAF mutation does not necessarily 'drive' more rapid tumour growth but is associated with poorer MSS in patients with early‐stage disease.